Service for victims of crime VDS info and victims’ support: Analysis of the previous work - Ćopić Sanja M.; Nikolić Jasmina (Temida)
The first victim support service in our country VDS info and victims’ support started with its work in April 2003 within the Victimology Society of Serbia. This service is aimed at victims of crime (women and men), primarily at victims of violent crime, but also of some forms of property crime (such as burglary). The aim of the Service is to offer victims of crime information on their rights and the ways of how to realize them, emotional support, as well as to refer them to other institutions/organizations depending on the certain victim’s needs. Coordinators and volunteers, who passed the appropriate training, are responsible for that. Bearing that in mind, this paper will give the brief glens on the Service itself, its organization and the way of work, followed by the analysis of the results of previous work.